THE ALSHAR EPITHERMAL AU-AS-SB-TL DEPOSIT, SOUTHERN MACEDONIA - Volkov A.V.; Kochneva N.T.; Tomson I.N.; Serafimovski T.; Tasev G. (My University, 2006)
The results of tectono-metallogenic, geological-structural, mineralogical, isotopic, and thermobarogeochemical studies at the Alshar deposit and in the adjacent area are discussed. The data obtained show that the gold mineralization at the deposit is similar to that observed at the Carlin-type deposits in the western United States. Similar characteristics include the Au-As-Sb-Tl-Hg geochemical assemblage; low Pb, Zn, Cu, and Ag contents in ore; widespread jasperoid and argillic metasomatic alterations of host siliciclastic-carbonate sedimentary rocks; and the spatial relations to fault zones. At the same time, the Alshar deposit differs from the Carlin-type deposits by the following features: (1) Pliocene age of mineralization, (2) expansion of mineralization over younger volcanics, (3) a high Tl grade in ore, and (4) localization of the ore field in a long-lived central-type magmatic structure. The results obtained can be used as an exploration model. © Pleiades Publishing, Inc. 2006.
Keywords: Pliocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен